Gastric cancer – clinical and epidemiological aspects. (September 2016) - Venerito, Marino; Link, Alexander; Rokkas, Theodoros; Malfertheiner, Peter
Abstract: Gastric cancer (GC) ranks fifth for cancer incidence and second for cancer deaths. Epidemiological data showed that survivors of Hodgkin's lymphoma and patients with pernicious anemia etiologically linked to autoimmune gastritis are at increased risk of GC. Screening of patients with autoimmune thyroid disease by means of pepsinogen (PG) I and PG I/II detected autoimmune gastritis with oxyntic gastric atrophy in one of four patients and may be recommended for GC prevention purposes. The International Agency for Research on Cancer reported a positive association between consumption of processed meet and increased GC risk. A new GC risk prediction model based on biological markers, age, gender, smoking status, family history of GC, and consumption of highly salted food showed good predictive performance, and might prompt individuals to modify their lifestyle habits, attend regular check‐up visits or participate in screening programs. A novel GC classification based on gene expression of primary resected cancers correlated with clinicopathological features. Noncoding RNA for GC screening remains the focus of multiple studies. Patients with early GC undergoing endoscopic resection are more likely to develop metachronous lesions than patients undergoing surgery and endoscopic surveillance is warranted in this special cohort. The addition of gastrectomy to chemotherapy did not improve survival of patients with advanced GC and a single noncurable factor. Apatinib, a novel oral vascular endothelial growth factor receptor 2 tyrosine kinase inhibitor, improved the median overall survival of patients with advanced GC and progressive disease after two or more lines of prior chemotherapy of nearly 3 months.